Effect of a feed supplement containing probiotics on fecal score and clinical parameters in dogs with chronic kidney disease and intestinal disorders: A pilot study - Francesca Perondi; Ilaria Lippi; Natascia Bruni; Nicolò Lonigro; Elisa Martello (Open Veterinary Journal)
Background: Chronic kidney disease (CKD) in dogs is often accompanied by dysbiosis and abnormal gut microbiota composition, leading to gastrointestinal issues. Probiotics, including Lactobacillus acidophilus, Enterococcus faecium, and Saccharomyces cerevisiae, have shown promise in maintaining a healthy gut microbiota in both healthy and CKD animals.